2017
DOI: 10.2174/1381612823666170112124303
|View full text |Cite
|
Sign up to set email alerts
|

A New Vaccine Delivery Vehicle and Adjuvant Candidate: Bordetella pertussis Inactivated Whole Cells Entrapped in Alginate Microspheres

Abstract: There is no doubt about the whole cell pertussis vaccine efficacy, but it is necessary to improve the vaccine quality specially to decrease its toxicity by obtaining good immunogenicity with low bacterial content. In this work, under optimum condition inactivated B. pertussis bacteria cells entrapped with alginate microparticles were fabricated and in vivo immunogenicity and ptency of new microparticle based vaccine were evaluated in mice. Microspheres loaded with inactive B. pertussis bacterium cells were pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…This process is vital for diseases due to multiple virulent serotypes/serogroups in circulation. In our earlier studies, oral MPs with several vaccines including pertussis, typhoid and tuberculosis vaccine have shown promising outcome in animal models [40][41][42][43]. The present study aligns with the previous observations and holds promise as the next generation vaccine formulation strategy for pneumococcal disease.…”
Section: Discussionsupporting
confidence: 88%
“…This process is vital for diseases due to multiple virulent serotypes/serogroups in circulation. In our earlier studies, oral MPs with several vaccines including pertussis, typhoid and tuberculosis vaccine have shown promising outcome in animal models [40][41][42][43]. The present study aligns with the previous observations and holds promise as the next generation vaccine formulation strategy for pneumococcal disease.…”
Section: Discussionsupporting
confidence: 88%
“…Attenuated Brucella melitensis encapsulated in alginate microspheres induces cell-mediated and antibody-mediated immune responses that are greater than freely suspended cells, and was effective at reducing the bacterial burden in mouse tissues [25]. Alginate encapsulation has also been effectively used to stimulate protection against Yersinia ruckeri in rainbow trout [28], Piscirickettsia salmonis in salmon [29], and Bordetella pertussis in mice [30]. Therefore, in theory, when used as a vaccine vehicle alginate encapsulation should prevent the immediate clearance of the attenuated strain, allowing the agent to be slowly released over an extended period of time, and continuously stimulate the immune system.…”
Section: Introductionmentioning
confidence: 99%
“…Anugraha et al (2015) demonstrated that PLA microspheres containing a recombinant vaccine candidate against Lymphatic Filariasis (Gyapong et al, 2005;Hoerauf et al, 2011) demonstrated high immunogenicity compared with the vaccine alone or mixed with the commercial adjuvant alum and provided a high level of protection after a single dose administration (Anugraha et al, 2015). Similarly, high immunogenicity was observed when inactivated B. pertussis (Zepp et al, 2011) bacterial cells were entrapped inside microparticles made from alginate, compared with alum absorbed vaccines (Dounighi et al, 2017). Liu et al showed that a stable formulation of a polycarbonate microsphere with the tetanus toxoid antigen by the water-in-oil-in-water evaporation technique exhibited low toxicity and provided protection against the toxin challenge, indicating that the polycarbonate microsphere could act as an adjuvant (Guillaume & Mespouille, 2014).…”
Section: Microparticlesmentioning
confidence: 99%
“…Finally, vaccines require adjuvants to elicit the desired immune response and excipients to maintain stability (Sivakumar et al, 2011). The advantage of a vaccine delivery device is that it offers space for including different excipient and adjuvants, and the device itself can provide adjuvanticity (Dounighi et al, 2017; Guillaume & Mespouille, 2014).…”
Section: Introductionmentioning
confidence: 99%